Foreign residency and residential segregation. The relationship between the spatial distribution of migrants and public housing in Bologna - Maggio, Manuela; Bergamaschi, Maurizio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
Whereas Italy has always been identified as a country of emigration, it is now a landing place. Despite the evolution of the migratory phenomenon has taken place over a few decades, it has an absolutely heterogeneous migratory profile due to the so-called "globalization of migrations". Today, the foreign one is a stable presence in Italy, but forms of discrimination and inequality related to being a foreigner persist and the reception of migrants still presents several critical issues. In this contribution we present an empirical study that contributes to the reflection about the peculiarities of the Italian context and we focus on the municipality of Bologna. On the one hand we aim to enrich the reflection on the concept of spatial segregation. On the other hand we will emphasize the role played by the welfare tools available in the housing sector on immigrant’s integration. We will use second level quantitative data and we will verify two research hypotheses: 1. at the local level, the administrative division of the census track could represent the space of segregation of the foreign population through the concentration of immigrants people in interstitial spaces; 2. there is a positive relationship between the spatial arrangement of public housing units and the spatial over-representation of the foreign population. Keywords: migration, segregation, suburbs, social housing, housing welfare